2015
DOI: 10.1021/acsphotonics.5b00130
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of the Evanescent Field of Free Electrons

Abstract: A nanoscale plasmonic metal film can amplify free-electron evanescent fields, leading to strongly enhanced light emission via Smith-Purcell effect through a mechanism analogous to the 'poor-man's superlens' for optical evanescent field enhancement. We demonstrate that a layer of silver a few tens of nanometers thick can amplify the evanescent field of free electrons in the same way that the plasmonic metal acts on the evanescent field of light. The enhancement of the evanescent field of free electrons is studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 38 publications
0
28
0
Order By: Relevance
“…The Smith-Purcell effect critically depends on precise fabrication of such a periodic structure, which is why the substantial progress in nanofabrication techniques in recent years has revealed a large variety of new applications (e.g., Refs. [14][15][16][17][18][19][20]) based on the SmithPurcell effect. Interestingly, the inverse Smith-Purcell effect has also shown exciting possibilities [21,22], which consequently led to more advanced photonic crystal structures being used as promising platforms for particle acceleration by light excitation of a periodic structure [23][24][25].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The Smith-Purcell effect critically depends on precise fabrication of such a periodic structure, which is why the substantial progress in nanofabrication techniques in recent years has revealed a large variety of new applications (e.g., Refs. [14][15][16][17][18][19][20]) based on the SmithPurcell effect. Interestingly, the inverse Smith-Purcell effect has also shown exciting possibilities [21,22], which consequently led to more advanced photonic crystal structures being used as promising platforms for particle acceleration by light excitation of a periodic structure [23][24][25].…”
mentioning
confidence: 99%
“…Such a measurement is particularly interesting for light-electron interactions involving structural defects, or when resolving the dynamics of surface-emitted light. In contrast, other CL setups collect the emitted light with a fiber [18,47] or a parabolic mirror, with the latter allowing angular-resolved CL collection [19,[48][49][50][51]. Yet, despite these techniques, no direct spatially resolved imaging of the light emission has been performed before, to the best of our knowledge.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Especially, the SPR-based terahertz (THz) light source has drawn a lot of attention in recent research 14 17 . Very recently, it has been found that SPR can be locked and enhanced at some emission wavelength and angle by excitation of SPs on the substrate 18 , 19 . This phenomenon is attributed to that the energy from electron concentrated in the excited SPs and then transformed into radiation via SPR mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Concurrently with Albert Polman's group in AMOLF, but a few days earlier, we published on the generation of travelling surface plasmon waves by free-electron impact [92]. We also demonstrated amplification of the evanescent field of free electrons [93]. We developed a nanoscale analogue of a free electron light source by demonstrating that the passage of a free-electron beam through a nanohole in a periodically layered metal-dielectric structure (nano undulator) creates a new type of tunable, nanoscale radiation source that we termed a 'light well' [94].…”
Section: Developing Metamaterials Technology: Switching and Tunabilitymentioning
confidence: 79%